Fisioterapia em cães com doença do disco intervertebral (hansen tipo i) toracolombar submetidos à descompressão cirúrgica - Andrades, Amanda Oliveira de (2017)
There are few reports in the veterinary literature concerning the use of physiotherapy in the postoperative recovery and quality of life of dogs with thoracolumbar intervertebral disc disease (IVDD). Therefore, this retrospective study aim was: to demonstrate the physiotherapeutic modalities used in the treatment of dogs with thoracolumbar IVDD experiencing different neurological dysfunction degrees and underwent surgical decompression; to report elements that determined the protocols changes (article 1); to compare the functional recovery and quality of life (QOL) of paraplegic dogs without deep pain perception that underwent a home physiotherapy protocol to those that received care in a specialized center (article 2). In the first article, 30 dogs with deep pain perception were included in the first physiotherapy session, presenting a range of clinical signs from ambulatory paraparesis to paraplegia. An initial protocol composed of different physiotherapeutic modalities was applied in all dogs, regardless of the degree of neurological dysfunction. The therapeutic exercises included in the initial protocol were selected according to the clinical evolution and acceptance of each patient, highlighting the inclusion and exclusion criteria of each modality. Eighty percent (80%) of the dogs manifested improvement in their neurological dysfunction degree before starting physical therapy and 93% were able to walk again (ambulatory paraparesis) at the end of physiotherapy. The number of sessions and recovery time were higher in patients with higher neurological dysfunction degrees. In the second article, 28 dogs underwent a home protocol (GA) while other 38 patients were cared in a specialized center (GB). Forty three percent (43%) of the GA animals recovered the ability to walk in an average of 40 postoperative (PO) days and 42% in an average of 36 days in GB. In 53% of the cases (35/66) the dogs remained paraplegic without deep pain perception at the end of physiotherapeutic protocols. There was no difference in rates and time of functional recovery between the groups. The evaluation of the animals survival time, euthanasia and the QOL score demonstrated that dogs that underwent a physiotherapeutic treatment in a specialized center probably were benefited by the close monitoring and orientation to owners until 90 days of PO.